2014
DOI: 10.1136/archdischild-2013-305331
|View full text |Cite
|
Sign up to set email alerts
|

Long QT molecular autopsy in sudden infant death syndrome

Abstract: ObjectiveTo describe experience of long QT (LQT) molecular autopsy in sudden infant death syndrome (SIDS).DesignDescriptive audit from two distinct periods: (1) A prospective, population-based series between 2006 and 2008 (‘unselected’). (2) Before and after 2006–2008, with testing guided by a cardiac genetic service (‘selected’). LQT genes 1, 2, 3, 5, 6 and 7 were sequenced. Next of kin were offered cardiac evaluation.SettingNew Zealand.Patients102 SIDS cases.InterventionsNil.Main outcome measuresDetection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…In New Zealand, the well-recognized risk factors of co-sleeping (bed sharing), accidental asphyxiation, and other environmental risk factors are particularly common among Maori and Pacific peoples, in whom SIDS predominates. 5 However, such features were also common in a large US series with a likely diagnostic rate of 13%. 7 A good cardiac genetic service is multidisciplinary, usually led by cardiology or pediatric cardiology, with access to electrophysiological expertise, clinical and molecular genetics, genetic counseling, and psychological support.…”
Section: Cardiac Genetic Servicesmentioning
confidence: 94%
See 2 more Smart Citations
“…In New Zealand, the well-recognized risk factors of co-sleeping (bed sharing), accidental asphyxiation, and other environmental risk factors are particularly common among Maori and Pacific peoples, in whom SIDS predominates. 5 However, such features were also common in a large US series with a likely diagnostic rate of 13%. 7 A good cardiac genetic service is multidisciplinary, usually led by cardiology or pediatric cardiology, with access to electrophysiological expertise, clinical and molecular genetics, genetic counseling, and psychological support.…”
Section: Cardiac Genetic Servicesmentioning
confidence: 94%
“…3 They and others also identified that between 2% and 12% of Sudden Infant Death Syndrome (SIDS) cases were caused by mutations in the LQTS genes. [4][5][6][7] In New Zealand, an LQTS molecular autopsy was first tested in a retrospective cohort of individuals #35 years old, with DNA from the long-deceased victims being extracted from the archived neonatal screening (Guthrie) card. 8 Twenty-two percent of them were positive.…”
Section: Cardiac Genetic Investigation Of Autopsy-negative Sudden Deamentioning
confidence: 99%
See 1 more Smart Citation
“…In the most widely accepted definition, there is a graded classification based predominantly on the thoroughness of the autopsy investigation in excluding potential causes, and the possibility of positional asphyxia. 10,11 Type 1 occurs between the ages of 21 days and 9 months in otherwise healthy, normal infants, and there must have been a safe sleep environment, and a thorough autopsy. Type 1a includes cases where there has been extensive scene and laboratory investigations; if one of these investigations is absent, it becomes type 1b.…”
Section: Definition Of Sidsmentioning
confidence: 99%
“…Most SUDY because of LQTS occur during sleep or rest, and rare variants/mutations in SCN5A are by far the commonest, being found in 50% to 75%, compared with 8% to 10% in the LQTS registries. 11,[24][25][26] Genetic investigation of SIDS cases has had a variable yield of putative mutationsfrom <5% in prospective studies in the United States, New Zealand, and Germany 11,27,28 to a recent study from New York where 15% had rare variants or mutations, predominantly in SCN5A. 25 The first large study, from Norway 24 detected 26 rare variants among 201 cases and suggested 19 of these 26 (therefore, a total of 9.5%) were pathogenic mutations.…”
Section: In Cases Of Sids and Sudymentioning
confidence: 99%